PD-1 inhibitor-based adverse events in solid tumors: A retrospective real-world study - Huang, Guili; Liu, Songqing; Dong, Jie; Xi, Xin; Kong, Rui; Li, Wenjun; Du, Qian (Frontiers in Pharmacology, 2022)
Background & Aims: Immune checkpoint inhibitors (ICIs) have transformed the landscape of cancer treatment, and ICI-related toxicities (i.e., immune-related adverse events (irAEs) have been reported in many clinical studies. However, the toxicity data of real-world have not been fully assessed. Methods: Patients with histologically confirmed solid tumors who had been treated with PD-1 inhibitors were included in the study. Patient data were collected from electronic medical records, including basic characteristics, data of irAEs, management and outcome. Incidences of irAEs were pooled and compared, and the risk of irAEs was also analyzed. Results: A total of 362 solid tumor patients treated with sintilimab (n=171), camrelizumab (n=60), toripalimab (n=72), and pembrolizumab (n=59) were included. In total, any grade irAEs, grade 1-2 irAEs, and grade ≥3 irAEs accounted for 47.24%, 38.67% and 8.56% of cases, reapectively. Further, 29.24% of patients discontinued immunotherapy due to irAEs, with pneumonitis being the main reason for discontinuation. By comparing the toxicity profiles between different ICIs, we found that reactive capillary haemangiomas were camrelizumab-specific. Additionally, the frequency of irAEs was association with ICIs type, the pooled incidence (standardized rate) of irAEs related to sintilimab, camrelizumab, toripalimab and pembrolizumab were 55.56% (52.81%), 48.33% (55.55%), 33.33% (29.23%) and 38.98% (38.29%), respectively. Sintilimab and camrelizumab had higher incidences of any grade and grade 1-2 than toripalimab (55.56% vs. 33.33%, p=0.002; 48.54% vs. 25.00%, p=0.0001) and pembrolizumab (55.56% vs. 38.98%, p=0.0028; 48.54% vs. 25.42%, p=0.002), while the grade ≥3 irAEs of pembrolizumab (13.56%) were approximately 1.63- to 1.93-fold higher than other ICIs, and the standardized grade ≥3 of pembrolizumab was significantly higher than that of sintilimab (13.21% vs. 7.12%, p=0.026), especially for grade ≥3 pneumonitis. Multivariate analysis found that cumulative cycles of ICI (OR=1.081; 95% CI: 1.023–1.142; P=0.006), and lung cancer (OR=1.765; 95% CI: 1.105–2.820; P=0.017) were independent risk factors for irAEs. Conclusions: The frequency of irAEs is associated with ICI type. The pooled incidence of irAEs related to sintilimab and pneumonitis caused by pembrolizumab were higher. These data indicate the importance of having different monitoring priorities for different PD-1 inhibitors.